Sociology : the basics - Plummer, Kenneth (New York, 2022)
A lively, accessible and comprehensive introduction to the diverse ways of thinking about social life, Sociology: The Basics has been translated into six languages. The volume is packed with thought-provoking summaries, questions, quotations and activities. It offers an absorbing narrative about what we mean by the social, and how we can think about it, weaving in discussions of the personal, the political and social change, along with concepts and vivid contemporary examples, and answering questions such as: What is the scope, history and purpose of sociology? How do we cultivate ways of understanding society and the social'? What is the state of the world we live in today? How do we analyse suffering and inequalities? What are key methods and tools for researching and thinking about society? How has digitalism reshaped sociology and its method? How might sociology help us understand the changes brought about by Covid-19? Does sociology have values? What is the role of sociology in making a better world? In this thoroughly revised and updated Third edition the reader is encouraged to think critically about the structures, meanings, histories and cultures found in the rapidly changing world we live in. With tasks to stimulate the sociological mind and suggestions for further reading both within the text and on an accompanying website, this book is essential reading for all those studying sociology and those with an interest in how the modern world works.